Obstructive breathing disorders in sleep: Obstructive sleep apnea-hypopnea syndrome and upper airway resistance syndrome (Portuguese Journal of Family Medicine and General Practice, 2006)
Respiratory disorders are obstructive diseases of high prevalence, associated morbidity and mortality important. In recent decades it has been indicated as a risk factor in heart disease and vascular. Daytime sleepiness resulting from sleep fragmentation characteristic of these entities has obvious consequences on quality of life of the patient and occupational safety and road. We present a review of the clinical diagnosis and treatment of sleep disordered breathing.